2019
DOI: 10.3390/cancers11040452
|View full text |Cite
|
Sign up to set email alerts
|

TERT Promoter Mutations are Associated with Visceral Spreading in Melanoma of the Trunk

Abstract: Survival predictions are currently determined on the basis of NRAS/BRAF mutations, even though TERT promoter mutations have been recently associated with a poor prognosis in stage I-II melanomas. Usually, it is not recommended to perform a mutational test on primary melanoma, as the results do not always reflect the mutational status of metastases. In particular, trunk melanomas have been reported to have an unfavourable prognosis. A series of 105 advanced melanoma patients were analysed by TERT promoter Sange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…An evaluation with cross-sectional imaging is also necessary for an accurate staging according to AJCC guidelines, which is still the best prognosis predictor [19]. Our results corroborate and expand the results of Osella-Abate et al [13], which already suggested that this analysis could be first implemented in melanomas arising in the trunk, be-cause their rate of visceral metastasis seems to be greater than in any other location. Comparing with SLN biopsy, TERTp mutations have the advantage of being easily searched for during the normal staging process, in a small fragment of resected tumour samples, using common laboratory techniques.…”
Section: Discussionsupporting
confidence: 87%
“…An evaluation with cross-sectional imaging is also necessary for an accurate staging according to AJCC guidelines, which is still the best prognosis predictor [19]. Our results corroborate and expand the results of Osella-Abate et al [13], which already suggested that this analysis could be first implemented in melanomas arising in the trunk, be-cause their rate of visceral metastasis seems to be greater than in any other location. Comparing with SLN biopsy, TERTp mutations have the advantage of being easily searched for during the normal staging process, in a small fragment of resected tumour samples, using common laboratory techniques.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the increase in TERT expression may lead to the unlimited proliferative capacity of tumor cells, which is an important factor in tumorigenesis 23 . TERT mutations are also outlined as markers of tumor aggressiveness and poor prognosis in several human cancer types 24‐28 . A recent study revealed that in bladder cancer, TERT promoter mutation appeared to be a potential predictive marker of response to Bacillus Calmette‐Guérin treatment which was regarded as one of the first and most successful oncological immunotherapy 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the promoter region of the telomerase reverse transcriptase gene (TERTprom), along with mutations in BRAF/NRAS, are the most frequent genetic alterations detected in melanoma [3]. While the prognostic significance of BRAF/NRAS mutations in melanoma is still debated, numerous studies reported that TERTprom mutations associate with poor prognosis [4][5][6][7]. TERT encodes the catalytic subunit of the telomerase complex, which plays a key role in maintaining chromosomal telomere length, thus supporting cell survival.…”
Section: Introductionmentioning
confidence: 99%